Substantiation of system functional indicators for small derivative hydroelectric power stations - Бабич, Михайло Іванович (Technology audit and production reserves, 2015)
This article discusses substantiation of the indicators for small derivative hydroelectric power stations for electricity production through the development of hydropower of small rivers. The basis of the substantiation of these indicators is the coordination of the characteristics of the components of derivative hydroelectric power stations (hydro turbine and derivational channel) with the characteristics of the river (pressure, water flow). This coordination is done in the "river – SHPS" system bringing received systemic functional parameters characterizing the results of the hydroelectric power stations with certain characteristics in areas of the river. The optimization criteria for indicators of derivative hydroelectric power station for a particular area of the river are proved. There are incomes from energy that produced and sold to the grid. Comparing the results of different variants of hydroelectric power stations in the "river – SHPS" system, by this criterion, functional system indicators for small derivative hydroelectric power stations on small rivers are proved.